2016
DOI: 10.1007/s10517-016-3422-2
|View full text |Cite
|
Sign up to set email alerts
|

Serological Analysis of Immunogenic Properties of Recombinant Meningococcus IgA1 Protease-Based Proteins

Abstract: Using the genome sequence of IgA1 protease of N. meningitidis of serogroup B, four recombinant proteins of different structure and molecular weight were constructed. These proteins were equal in inducing the formation of specific antibodies to IgA1 protease and had protective properties against meningococci. In the sera of immunized mice, anti-IgA1 protease antibodies were detected by whole-cell ELISA, which indicated the presence of IgA1 protease on the surface of these bacteria. We hypothesized that the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…IgA proteases in other bacteria are components of autotransporter molecules, enhance bacterial invasion of mucosal surfaces, and assist in bacterial escape from host defenses (Mistry and Stockley, 2006). In addition, bacterial IgA proteases are immunogenic and stimulate local and systemic antibodies in infected hosts (Morelli et al ., 1994; Kirkeby et al ., 2000; Kotelnikova et al ., 2016).…”
Section: Virulence Factors and Potential Immunogensmentioning
confidence: 99%
“…IgA proteases in other bacteria are components of autotransporter molecules, enhance bacterial invasion of mucosal surfaces, and assist in bacterial escape from host defenses (Mistry and Stockley, 2006). In addition, bacterial IgA proteases are immunogenic and stimulate local and systemic antibodies in infected hosts (Morelli et al ., 1994; Kirkeby et al ., 2000; Kotelnikova et al ., 2016).…”
Section: Virulence Factors and Potential Immunogensmentioning
confidence: 99%
“…The antibody titer to recombinant proteins in the human and animal sera was determined by ELISA [2].…”
Section: Methodsmentioning
confidence: 99%
“…Experimental confirmation of the protective activity of IgA1 protease is shown in a small number of works. In a series of works [64][65][66][67][68][69][70][71][72][73][74] in animal experiments, it was shown that native IgA1 protease isolated from a live virulent culture of N. meningitidis serogroup A, as well as recombinant IgA1 proteases of N. meningitidis serogroup B in active or mutant forms, and some truncated analogs of these proteins have high immunogenic and protective activity.…”
Section: Iga1 Protease and Its Fragments As A Basis For The Creation Of Therapeutic And Preventive Agentsmentioning
confidence: 99%
“…It was also shown that specific antibodies formed upon immunization of animals with IgA1 protease analogs or upon infection with meningococcus are capable of binding not only to the secreted enzyme, but also to the surface of microbial cells [66].…”
Section: Iga1 Protease and Its Fragments As A Basis For The Creation Of Therapeutic And Preventive Agentsmentioning
confidence: 99%